Heat transfer parameters for two-phase models of packed beds at low reynolds numbers. - Benito, Regano G., Ph D.
A review, consolidation and summary of the available correlations and data from various literatures were made for the parameters representing the mechanisms of heat transfer for fluid flows in packed beds at low Reynolds numbers. These parameters are the axial dispersion coefficient, the effective solid phase conductivity, the particle and effective heat transfer coefficient. Values of these parameters are required in the two phase models of packed bed. Due to lack of data from heat transfer experiments, the possibility of obtaining these parameters from mass transfer experiments was explored on the assumption of direct analogy between mass and heat transfer.